Transponering eller transformasjon? Noen refleksjoner om oversettelse, med utgangspunkt i Antoni Liberas roman Madame og andre slaviske litteraturverker - Brodal, Jan (Folia Scandinavica Posnaniensia, 2007)
The article “Transponering eller transformasjon?” (“Transposition or Transformation?”) sketches two common types of literary translation on the base of some works by classic and modern writers from Slavic literatures. The translators adhering to what may be called the school of Transposition, strive to attain a high degree of identity with the original, those preferring the method of Transformation permit themselves various liberties, as witnessed by Agnieszka Kołakowska’s English translation of Antoni Libera’s novel Madame, where even some of the characters’ names in the original are changed in the translation. Similar transformations can be found in Norwegian translations of the novels of Dostoevsky during the years after the Second World War.